Aging in place in rural Northeast China: a mixed methods examination of the influence of social capital on mental well-being in middle and late adulthood - Gao, Yunfei; Wu, Jing (Frontiers in Public Health, 2024)
The rural development strategy in contemporary China has evolved from focusing solely on “absolute poverty alleviation” to addressing multiple dimensions, including “targeting relative poverty and revitalizing the entire rural area.” Using a mixed-methods approach, our study aimed to examine whether and how social capital, particularly social support and social trust, influences the mental well-being of middle-aged and older people aging in place in a remote rural Northeast area of China, exploring three constructs: life purpose, self-actualization, and capability. Our quantitative findings revealed that higher levels of social support and social trust were positively related to higher levels of life purpose. Increased social support was positively related to increased life purpose through increased social trust. However, the associations between social support, social trust, and the constructs of self-actualization and capability were not substantiated after controlling for covariates. Our interview data illuminated how middle-aged and older people perceived the interplay between social support, social trust, and mental well-being.